Innovative Technology Using Virtual Reality in the Treatment of Pain: Does It Reduce Pain via Distraction, or Is There More to It?. Issue 1 (31st August 2017) - Gupta, Anita; Scott, Kevin; Dukewich, Matthew
Abstract: Objective: Virtual reality (VR) is an exciting new technology with almost endless possible uses in medicine. One area it has shown promise is pain management. This selective review focused on studies that gave evidence to the distraction or nondistraction mechanisms by which VR leads to the treatment of pain. Methods: The review looked at articles from 2000 to July 29, 2016, focusing on studies concerning mechanisms by which virtual reality can augment pain relief. The data was collected through a search of MEDLINE and Web of Science using the key words of "virtual reality" and "pain" or "distraction." Results: Six studies were identified: four small randomized controlled studies and two prospective/pilot studies. The search results provided evidence that distraction is a technique by which VR can have benefits in the treatment of pain. Both adult and pediatric populations were included in these studies. In addition to acute pain, several studies looked at chronic pain states such as headaches or fibromyalgia. These studies also combined VR with other treatment modalities such as biofeedback mechanisms and cognitive behavioral therapy. Conclusions: These results demonstrate that in addition to distraction, there are novel mechanisms for VR treatment in pain, such as producing neurophysiologic changes related to conditioning and exposure therapies. If these new mechanisms can lead to new treatment options for patients with chronic pain, VR may have the ability to help reduce opioid use and misuse among chronic pain patients. More studies are needed to reproduce results from prospective/pilot studies in large randomized control studies.